Brain hyperserotonemia causes autism-relevant social deficits in mice - Tanaka, Miho; Sato, Atsushi; Kasai, Shinya; Hagino, Yoko; Kotajima-Murakami, Hiroko; Kashii, Hirofumi; Takamatsu, Yukio; Nishito, Yasumasa; Inagaki, Masumi; Mizuguchi, Masashi; Hall, F. Scott; Uhl, George R.; et al. (Molecular autism, 2018)
Background Hyperserotonemia in the brain is suspected to be an endophenotype of autism spectrum disorder (ASD). Reducing serotonin levels in the brain through modulation of serotonin transporter function may improve ASD symptoms. Methods We analyzed behavior and gene expression to unveil the causal mechanism of ASD-relevant social deficits using serotonin transporter ( Sert ) knockout mice. Results Social deficits were observed in both heterozygous knockout mice (HZ) and homozygous knockout mice (KO), but increases in general anxiety were only observed in KO mice. Two weeks of dietary restriction of the serotonin precursor tryptophan ameliorated both brain hyperserotonemia and ASD-relevant social deficits in Sert HZ and KO mice. The expression of rather distinct sets of genes was altered in Sert HZ and KO mice, and a substantial portion of these genes was also affected by tryptophan depletion. Tryptophan depletion in Sert HZ and KO mice was associated with alterations in the expression of genes involved in signal transduction pathways initiated by changes in extracellular serotonin or melatonin, a derivative of serotonin. Only expression of the AU015836 gene was altered in both Sert HZ and KO mice. AU015836 expression and ASD-relevant social deficits normalized after dietary tryptophan restriction. Conclusions These findings reveal a Sert gene dose-dependent effect on brain hyperserotonemia and related behavioral sequelae in ASD and a possible therapeutic target to normalize brain hyperserotonemia and ASD-relevant social deficits.